Batik wastewater treatment using synthetic and natural-based coagulant / Non Daina Masdar - Masdar, Non Daina (2004)
Batik industries generate varieties of wastewater from cleaning, processing and dyeing processes. Disposal of the batik wastewater with pH ranges from 4 to 13 could affect an environmental problem due to the high content of dissolved solid and toxic compounds as well as coloured bodies. Nowadays, polymers application is a common industrial practice in wastewater treatment. A coagulant, namely KN1 was developed from a local plant, and employed in a newly treatment system called ALL-IN-ONE CONCEPT (AOC). The AOC wastewater treatment plant was designed to use KN1 in order to meet the requirements of Environmental Quality Act (EQA). The pilot plant is able to chemically and physically treat the batik wastewater in the same reaction tank, hence minimizing the area occupied and modification of the existing batik making apparatus. The treatment started with the coagulation and flocculation process, followed by sedimentation of solid particles finally filtration using specially designed activated carbon column. The most suitable pH for KN1 and hydrochloric acid (HCl) for the coagulation and flocculation process ranges from 1 to 2.5 with 8 x 4 mm non-washing granular activated carbon (GAC). The results show that the average chemical oxygen demand (COD) and biochemical oxygen demand (BOD) reduction were 91 per cent and 72 per cent respectively. The average removal of total solids (TS), total suspended solids (TSS) and volatile suspended solids (TSS) was 99.8 per cent. The turbidity was reduced from 447 NTU to colourless after 50 hours of treatment. Heavy metal constituents show a reduction up to 80 per cent as well as oil and grease constituent. Despite the biodegradable properties, KN1 also shows the non-selectivity in treating batik wastewater compared to other coagulant such as Polyaluminium Chloride (PAC) and Polydadmac (PDMC).